(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The recognition of faces is of great significance for real worlds applications like video surveillance, classroom students attendance recording, human-machine interaction, security systems etc. It is still several challenges to detection and recognition for recognising multiple faces because it is not easy for detecting multiple faces in one frame, it is also hard to recognise faces with low resolution. Compared to machine learning traditional approaches, approaches based-on deep learning shown better performance in terms of processing speed and accuracy in face recognition. Our method uses a combination of Viola Jones, Face-net and Support Vector Machine (SVM), and achieved an accuracy of 94% for 100 person through 166s and for real time face recognition, it achieved an accuracy of 100% for 10 frames through 9 seconds.